Model to measure the adequacy of retirement funds. - Koh, Siew May. (2008)
This report serves to analyse the adequacy of retirement funds using a model based on the replacement ratio.The replacement ratio is influenced by the factors- housing loan amount, annual salary, savings rate, retirement age and the present age that an individual begins to save. Analysis of the factors can be used to determine the expenditure patterns - housing loan and the savings rate that an individual should adopt.